Genomewide signatures of selection in Epichloë reveal candidate genes for host specialization. Issue 15 (27th April 2018) - Schirrmann, Melanie K.; Zoller, Stefan; Croll, Daniel; Stukenbrock, Eva H.; Leuchtmann, Adrian; Fior, Simone
Abstract: Host specialization is a key process in ecological divergence and speciation of plant‐associated fungi. The underlying determinants of host specialization are generally poorly understood, especially in endophytes, which constitute one of the most abundant components of the plant microbiome. We addressed the genetic basis of host specialization in two sympatric subspecies of grass‐endophytic fungi from the Epichloë typhina complex: subsp. typhina and clarkii . The life cycle of these fungi entails unrestricted dispersal of gametes and sexual reproduction before infection of a new host, implying that the host imposes a selective barrier on viability of the progeny. We aimed to detect genes under divergent selection between subspecies, experiencing restricted gene flow due to adaptation to different hosts. Using pooled whole‐genome sequencing data, we combined F ST and D XY population statistics in genome scans and detected 57 outlier genes showing strong differentiation between the two subspecies. Genomewide analyses of nucleotide diversity (π), Tajima's D and d N/ d S ratios indicated that these genes have evolved under positive selection. Genes encoding secreted proteins were enriched among the genes showing evidence of positive selection, suggesting that molecular plant–fungus interactions are strong drivers of endophyte divergence. We focused on five genes encoding secreted proteins, which were further sequenced in 28 additional isolates collected across Europe to assess genetic variation in a larger sample size. Signature of positive selection in these isolates and putative identification of pathogenic function supports our findings that these genes represent strong candidates for host specialization determinants in Epichloë endophytes. Our results highlight the role of secreted proteins as key determinants of host specialization. Abstract : see also the Perspective by Gladieux